Illustrations - Richardson, Graham T. author. aut Link
337 p.
Keywords: person to prepare illustration copy at a pre-professional level-copy that is, however, often usable for routine purposes-and/or to communicate better with graphics spe cialists who will prepare the final illustrations. The skills necessary to take the final step of producing finished camera-ready illustrations are, unfortunately, based very much on actual hands-on experience and are thus beyond the ability of this or any other book to instill satisfactory competence in. Illustrations should also prove to be a highly useful reference work for professional illustrators. The wide variety of train ing and work experiences by which they have acquired their skills may not have provided full acquaintance with all of the exceptionally diverse kinds of information to be found here. There are, moreover, few disciplines whose practition ers cannot profit from an invigorating refresher course. After nearly seven years of work, then, I am pleased to put forward a book with many answers pertaining to the proper selection and preparation of informational illustrations. All such questions and their actual solutions, however, must re main up to you, the inquiring and attentive reader.